PTH-139 Usage of transmural metal stents for endoscopic ultrasound guided drainage of pseudocysts may lead to lower reintervention rates. (17th June 2017) - Ramesh, J; Saunders, R; Evans, J; Ghaneh, P; Raraty, M; Yip, V; Barkatali, R; Hughes, F; McCready, R; Cicconi, S; Sutton, R; Neoptolemos, JP; et al.
Abstract : Introduction: Endoscopic ultrasound (EUS) guided drainage is now the first line treatment for drainage of symptomatic pancreatic pseudocysts. This study investigates the effects of metal vs. plastic transmural stents. The primary outcome measure was defined as rate of reintervention for pseudocyst following stent. Method: A prospectively maintained database from 2011–2016 was analysed. Fluid collections were characterised by CT imaging and EUS. All patients were discussed at multidisciplinary meeting prior to intervention. Results: 74 patients with pseudocysts were included in this analysis. There was no significant difference in patient demographics or indication for intervention between the groups. Metal stents were placed in 38 (51%) patients. Three patients (8%) with metal stents required further intervention compared to 11 patients (31%) with plastic stents (p=0.037). Technical success was similar between groups; 100% for metal vs 97% for plastic stents. At 6 weeks following procedure, pseudocyst drainage was achieved in 33/35 patients using metal vs 27/36 of the plastic stent group (p=0.046). 25 patients with metal stents achieved pseudocyst drainage at 6 months vs 23 (p=0.25) who had plastic stents. Early adverse events were less common in the metal stent group (8%) vs 33% with plastic stents (p=0.009). Conclusion: Use of metal transmural stents for drainage of pancreatic pseudocysts may reduce reintervention rates and causes fewer adverse events compared to plastic stents. Drainage with metal stents is most effective by 6 weeks, with little difference between metal vs. plastic stents by 6 months. Disclosure of Interest: None Declared